Level of Acceptability of Mashed Cheese Squash to Selected Grade 12 and Faculty Members of Home Economics Strand in Bestlink College of the Philippines, S.Y. 2019–2020 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Squash is one of the most underrated vegetables that people tend to overlook.Squash (under genus Cucurbita) isa variety of blooming plants in the gourd family (Cucurbitaceae), many of which are widely cultivated as vegetables for food and livestock feed. Squashes are local to the new world, where they are developed by local farming groups before European settlement. The product of the consumable species is normally filled in as a cooked vegetable, and the seeds and blooms may be cooked and eaten. Summer and winter squash are full of nutrients,containing trace amounts of B vitamins and healthy doses of iron, calcium, magnesium. and potassium. The rinds of squash contain beta-carotene. Squash is a staple food for many weight-loss regimens because of its potential health benefits. The researchers chose respondents composed of Home Economics Strand students and teachers. The researchers used a random sampling technique in this study. The research design used in this study was an experimental method. The researchers also used a survey as an instrument to gather information. The findings of this study showed that for students, the composite weighted mean in terms of taste was 3.8, that in terms of aroma was 3.5, that for nutritional value was 3.8, and that in terms of the presentation was 4.0. The total composite weighted mean was3.78, which had the verbal interpretation of strongly agree. For teachers, the composite weighted mean in terms of taste was3.7, that in terms of aroma was 3.5, that in terms of nutritional value was 4, and that in terms of the presentation was 3.5. The total composite weighted mean was3.68, which had the verbal interpretation of strongly agree. In terms of taste, the respondents indicated that mashed cheese squash is not too salty, has a well-blended flavor, and is delicious. In terms of aroma, the respondents agreed that mashed cheese squash has a pleasant smell, and all respondents strongly agreed that it does not have a foul odor. The respondents also indicated that mashed cheese squash has a pleasing smell that makes you lick your lips. In terms of aroma, the respondents said that it influences the taste.
Keywords: mashed cheese squash